SYSTEMATIC LITERATURE REVIEW: ANALISIS PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA DI INDONESIA - Idafia Tabuni; Agustina Asso; I Gusti Ayu Ngurah Kade Sukiastini; Matilda Serfi Desta; Yuliana Eva; Lilian Anggriani Tebiari (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
Curriculum changes in Indonesia represent an adaptive response to the dynamics of the times, societal needs, and global developments in education. The Merdeka Curriculum, launched in the 2022/2023 academic year by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), offers freedom and flexibility for schools to determine learning materials that are relevant to students’ characteristics and needs. This approach aims to enable students to develop according to their potential through critical, high-quality, and adaptive learning. However, the implementation of the Merdeka Curriculum faces various challenges, such as the readiness of schools and teachers, limitations in digital infrastructure, and students’ mental readiness for independent learning. This study employs a qualitative Systematic Literature Review approach using the PRISMA method to analyze the problems encountered in implementing the Merdeka Curriculum. The analysis of 15 articles indicates that the main obstacles include teachers’ limited understanding of the curriculum, inadequate digital facilities, time management issues, students’ mental readiness, and insufficient curriculum socialization for parents. These findings emphasize the importance of adequate training, the improvement of digital infrastructure, and collaboration among various stakeholders to address these challenges and achieve the primary goal of improving educational quality and developing students’ potential. This study provides important insights for future educational policy development and highlights the need for collaborative efforts to ensure the effective implementation of the Merdeka Curriculum, thereby delivering optimal benefits for learners in Indonesia. ABSTRAK Perubahan kurikulum di Indonesia merupakan respons adaptif terhadap dinamika zaman, kebutuhan masyarakat, dan perkembangan pendidikan global. Kurikulum Merdeka, diluncurkan pada tahun ajaran 2022/2023 oleh Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi (Kemendikbudristek), menawarkan kebebasan dan fleksibilitas bagi sekolah dalam menentukan materi pembelajaran yang relevan dengan karakteristik dan kebutuhan siswa. Pendekatan ini bertujuan agar siswa dapat berkembang sesuai potensi mereka melalui pembelajaran kritis, berkualitas, dan adaptif. Namun, implementasi Kurikulum Merdeka menghadapi berbagai tantangan seperti kesiapan sekolah dan guru, keterbatasan sarana digital, dan kesiapan mental siswa untuk belajar mandiri. Penelitian ini menggunakan pendekatan kualitatif Systematic Literature Review dengan metode PRISMA untuk menganalisis problematika dalam penerapan Kurikulum Merdeka. Hasil analisis terhadap 15 artikel menunjukkan hambatan utama adalah kurangnya pemahaman guru terhadap kurikulum, keterbatasan sarana digital, pengelolaan waktu, kesiapan mental siswa, dan kurangnya sosialisasi kurikulum kepada orang tua. Temuan ini menekankan pentingnya pelatihan yang memadai, peningkatan sarana digital, dan kolaborasi antara berbagai pihak untuk mengatasi kendala tersebut dan mencapai tujuan utama peningkatan kualitas pendidikan dan pengembangan potensi siswa. Penelitian ini memberikan wawasan penting bagi pengembangan kebijakan pendidikan di masa mendatang dan menekankan perlunya upaya kolaboratif untuk memastikan implementasi Kurikulum Merdeka berjalan efektif, memberikan manfaat optimal bagi peserta didik di Indonesia.